EFFECTS OF KOH CONCENTRATION ON CHARACTERISTICS OF USED COOKING OIL LIQUID SOAP HAVING KALAMANSI CITTRUS FRAGRANCE - Devi Silsia; Laili Susanti; Reko Apriantonedi (Jurnal Agroindustri, 2017)
Used refined cooking oil can be used to make soap. An important factor in the manufacture of soap is the saponification reaction between bases (KOH) and fatty acids. The addition of citrus essential oil to the soap preparation can increase consumer acceptance. This study aims to determine the effect of KOH concentration on the characteristics of liquid soap and to determine the proper concentration of KOH to produce good quality of liquid soap. This research uses a factorial completely randomized design with one factor that is KOH concentration, consisting of three levels ie 25%, 30% and 35%. Characteristics of liquid soap observed were viscosity, foam height, pH, and free alkali content. The results showed that the concentration of KOH effect on the characteristics of  liquid  soap  produced. If  KOH concentration increases,  viscosity,  pH and alkali-free  alkali content of the liquid soap increased. The best KOH concentration is 25%.